Encapsulating peritoneal sclerosis: Your questions answered. Issue 2 (March 2023) - Pepereke, Shingai; Shah, Ankur D; Brown, Edwina A
Encapsulating peritoneal sclerosis (EPS) is a clinical syndrome hallmarked by the formation of a fibrous cocoon encapsulating the bowel resulting in morbidity and mortality. EPS is most frequently associated with peritoneal dialysis (PD), particularly with its discontinuation. While EPS is one of the most feared complications of PD, the majority of patients receiving PD will not go on to develop EPS. Risk factors for development include time on PD, some types of peritonitis and discontinuation of PD. Owing to its rarity, much of the knowledge of EPS comes from case series and registries and treatments are extrapolated from low-quality evidence. Malnutrition is a significant driver of mortality, and nutritional support is critical in management. We present a case of EPS and frequently asked questions including the definition, diagnosis, epidemiology, pathophysiology, risk factors, role of infection, management and roles of nutrition and surgery.